Implementasi Green Sukuk dalam Pembangunan Nasional: Analisis Fikih Muamalah terhadap Akad dan Pemanfaatan Aset - Muhammad Sauqi; Muh Arief Budiman; Hana A’isyah; Laila Syifa; Erza Aulia Rizki (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2026)
Green sukuk is a Sharia-compliant financial instrument that combines sukuk principles with sustainable financing aimed at environmental preservation. It is used to finance environmentally friendly projects, including renewable energy, sustainable transportation, waste management, and green infrastructure development. Indonesia is one of the countries actively issuing green sukuk as part of its national development financing strategy. This study aims to examine the implementation of green sukuk in national development from the perspective of fiqh muamalah, particularly regarding the contracts employed and the utilization of underlying assets. The research uses a literature review method by analyzing books, scientific journals, regulatory documents, and reports from relevant institutions. The findings show that green sukuk has become an effective financing instrument for supporting sustainable development while remaining consistent with Sharia principles. Its implementation is based on real underlying assets, employs contracts recognized in Islamic law, and avoids elements of riba, gharar, and maysir. Therefore, green sukuk not only contributes to financing environmentally sustainable development projects but also strengthens the integration of Islamic financial principles with environmental responsibility in the national development agenda.